STRATIFIKASI SOSIAL PENGAMBILAN KEPUTUSAN TENTANG KEUANGAN KELUARGA - Aris Wibowo (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2021)
Indonesian people who live in the village daily take care of plants in the fields and in the garden. The crop that is currently being planted is rice as a staple food. In managing rice, it is usually done by husband and wife together. Even so, the husband still does the heavy part and the wife does the light part, just like the husband who irrigates the plants and hoes and then the wife takes the weeds around the plants so that the plants grow optimally. The farmer household is one of the most decisive decision-making units in managing household needs, the decision-making process in the family is often dominated by the head of the family, researchers are interested in examining how social stratification and the implementation of rights and obligations of married couples in Banjarejo Village, Rejotangan District, Tulungagung Regency. This research method is qualitative with a field research approach. The data collection technique used in this study was conducted by interview. The results of the interview become primary data, this data is then analyzed using reduction techniques, presentation and conclusion drawing.